Metaboloepigenetics: Role in the Regulation of Flow-Mediated Endothelial (Dys)Function and Atherosclerosis - Francisco Santos; Hashum Sum; Denise Cheuk Lee Yan; Alison C. Brewer (Cells)
Endothelial dysfunction is the main initiating factor in atherosclerosis. Through mechanotransduction, shear stress regulates endothelial cell function in both homeostatic and diseased states. Accumulating evidence reveals that epigenetic changes play critical roles in the etiology of cardiovascular diseases, including atherosclerosis. The metabolic regulation of epigenetics has emerged as an important factor in the control of gene expression in diseased states, but to the best of our knowledge, this connection remains largely unexplored in endothelial dysfunction and atherosclerosis. In this review, we (1) summarize how shear stress (or flow) regulates endothelial (dys)function; (2) explore the epigenetic alterations that occur in the endothelium in response to disturbed flow; (3) review endothelial cell metabolism under different shear stress conditions; and (4) suggest mechanisms which may link this altered metabolism to the regulation of the endothelial epigenome by modulations in metabolite availability. We believe that metabolic regulation plays an important role in endothelial epigenetic reprogramming and could pave the way for novel metabolism-based therapeutic strategies.